The Development of Theory of Mind and Positive and Negative Reciprocity in Preschool Children - Schug, Joanna; Takagishi, Haruto; Benech, Catalina; Okada, Hiroyuki (Frontiers in Psychology, 2016)
This study examined the relation between the acquisition of false-beliefs theory of mind and reciprocity in preschoolers. Preschool-aged children completed a task assessing the understanding of false beliefs, and played an Ultimatum Game (UG) with another child in a face-to-face setting. Negative reciprocity was assessed by examining the rejection of unfair offers made by another child in the UG, while positive reciprocity by examining allocations made by participants in a Dictator Game (DG) following the UG. The results indicated that children who had passed a task assessing first-order false beliefs were more likely to make generous offers in a DG following a fair offer made by their partner in a proceeding UG, but that the false beliefs theory of mind was unrelated to the rejection of unfair offers in the UG.